Range of invasive meningococcal disease sequelae and health economic application - a systematic and clinical review - Jing Shen; Najida Begum; Yara Ruiz-Garcia; Federico Martinon-Torres; Rafik Bekkat-Berkani; Kinga Meszaros (BMC, 2022)
Highlights Invasive meningococcal disease survivors frequently suffer from variable sequelae. A broad sequelae map plus those relevant to economic evaluation (EE) were defined. Forty-four sequelae were selected: 30 physical/neurological and 14 psychological/behavioural. Eighteen EE-relevant sequelae included 14 physical/neurological and 4 psychological/behavioural Underreporting, family impact and multiple sequelae cases were critical gaps. A video summary linked to this article can be found on Figshare: https://doi.org/10.6084/m9.figshare.19753840 .